New Rules for a New Economy Employment and Opportunity in Post-Industrial America - Herzenberg, Stephen A.; Alic, John A.; Wial, Howard (Cornell University Press, 2018)
Three quarters of the American workforce is now employed in services, a substantial portion in low-paying, dead-end jobs. Can the service economy do as well by the American worker as the old manufacturing economy? Can the widely shared prosperity that accompanied steady increases in productivity and performance in manufacturing be replicated in the services? They can and they will, the authors of this timely book contend, but only if outmoded policies and practices are brought into line with the new economy. New Rules for a New Economy explains why this must be accomplished and how we can start.The authors call for new, decentralized institutions suited to a dynamic economy in which change is constant and rapid. In particular, they see a need for job ladders and worker associations that cut across firm boundaries. These institutions would foster individual and collective learning, mark out career paths, and facilitate coordination among both individuals and organizations in a networked economy. The authors propose new rules to reshape labor market institutions and policy, improving economic performance and opportunities for workers. Unusual in providing a comprehensive theoretical perspective that is grounded in detailed case research, this book points the way to a better future, not just for elite knowledge workers but for everyone
Description based on online resource; title from PDF title page (publisher's Web site, viewed 19. Feb 2019)
Keywords: Employment forecasting -- United States; Labor market -- United States; Manufacturing industries -- Employees -- Supply and demand -- United States -- Forecasting; Service industries workers -- Supply and demand -- United States -- Forecasting